Unusual absence of FRET in triazole bridged coumarin–hydroxyquinoline, an active sensor for Hg2+ detection. Issue 9 (29th July 2020) - Mondal, Surajit; Patra, Niladri; Nayek, Hari Pada; Hira, Sumit K.; Chatterjee, Soumit; Dey, Swapan
Abstract : A coumarin–quinoline conjugated triazole based sensor has been developed for the selective detection of Hg 2+ . The possible binding mode has been established via NMR, fluorescence spectroscopy and TDDFT calculations. Abstract : A triazole-bridged coumarin conjugated quinoline sensor has been 'click'-synthesized by Cu(i ) catalyzed Huisgen cycloaddition, and it exhibited high selectivity for toxic Hg 2+ . Surprisingly, no evidence of energy transfer from the quinoline moiety to coumarin has been found, substantiated by time-resolved fluorescence study. The possible binding mode of this sensor to Hg 2+ has been established via NMR study, steady-state and time-resolved fluorescence spectroscopy, which is further supported by TDDFT calculations. The sensor has been found to be cell membrane permeable and non-toxic, and hence is suitable for intracellular Hg 2+ detection.